D-Meson Azimuthal Anisotropy in Midcentral Pb-Pb Collisions at √ˢɴɴ =5.02 TeV - Acharya, S.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (American Physical Society, 2018)
The azimuthal anisotropy coefficient v2 of prompt D⁰, D⁺, D*⁺, and D⁺s mesons was measured in midcentral (30%–50% centrality class) Pb-Pb collisions at a center-of-mass energy per nucleon pair √ˢɴɴ = 5.02 TeV, with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decays at midrapidity, |y| < 0.8, in the transverse momentum interval 1 < Pᴛ < 24 GeV/c. The measured D-meson v2 has similar values as that of charged pions. The D⁺s v2, measured for the first time, is found to be compatible with that of nonstrange D mesons. The measurements are compared with theoretical calculations of charm-quark transport in a hydrodynamically expanding medium and have the potential to constrain medium parameters.
Keywords: Physics; Meson; Particle physics; Hadron; Pion; Nuclear physics; Anisotropy; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03